217k views
5 votes
Root( x-1 ) = 2 - root (x+3)

2 Answers

1 vote

Answer:


x=1

Explanation:


√(x-1) =2-√(x+3)

Square both sides.


\left(√(x-1)\right)^2=\left(2-√(x+3)\right)^2


x-1=x+7-4√(x+3)

Subtract x on both sides.


x-1-x=x+7-4√(x+3)-x


-1=-4√(x+3)+7

Subtract 7 on both sides.


-1-7=-4√(x+3)+7-7


-8=-4√(x+3)

Square both sides.


\left(-8\right)^2=\left(-4√(x+3)\right)^2


64=16x+48

Subtract 48 on both sides.


64-48=16x+48-48


16=16x

Divide both sides by 16.


(16)/(16) =(16x)/(16)


1=x

Switch sides.


x=1

User Wing Tang Wong
by
5.1k points
2 votes
Answer: x = 4

Explanation: root x-1 = 2- root x+3
First let’s take out the root by square both side by 2 we get:
x-1= 4-x+3
x-1 = -x+7
x+x = 7+1
2x= 8
x= 8/2=4
User Stanislav Smida
by
4.7k points